How to overcome a power deficit - Barsoux, Jean-Louis; Bouquet, Cyril (MIT, 2013)
At some point in their careers, most executives - even the most talented - will face a power deficit. Regardless of their titles and nominal responsibilities, they will confront situations in which they have insufficient influence and authority to get their job done effectively. Fortunately, two strategies can almost always help the sidelined executive capture more clout and build an enduring power base. A variety of situations can lead a manager into a power deficit. Demographics (race, ethnicity, gender or age) can contribute to the power-deficient executive's predicament, as can inexperience, poor reputation, personality, background, training or outlook. It can happen to people with high potential. It can even happen to executives who are already high performers. Typically, an executive winds up with a power deficit because he or she lacks one or more of the following power sources: legitimacy, critical resources or networks. The high level of interaction between these three sources of power means that a shortage in one can easily produce shortages in the other two. The authors argue that, generally, executives who have a power deficit can solve the problem in one of two ways: they must either play the game more effectively or change the game by, for instance, reshaping their role in the organization. The authors offer examples and recommendations and provide a short questionnaire to help managers identify potential power deficits. The good news is that the odds of success are good. The authors report that in their coaching work with 179 executives who wrestled with power deficits, only four failed to improve the situation.
Includes bibliographical references. - Description based on online resource; title from cover page (Safari, viewed April 22, 2015)
Keywords: Leadership; Industrial management; Gestion d'entreprise